Rare neurological presentations of Dengue Fever - Mathur, Navgeet; Mathur, Medha (Nepal Journal of Neuroscience, 2021)
In presence of abnormal neurological features infective, immunological and metabolic etiologies are also needed to be kept as possibility. Dengue fever may present with variety of neurological manifestations. This case series includes rare neurological presentation of dengue fever including first ever reported case of dengue fever induced bilateral abducens nerve palsy with another case of dengue cerebellitis. This case series along with previous studies suggest that imaging may be normal in these cases. This case series also highlighted the possible immunological etio-pathogenesis and role of steroids as treatment modality.